2015
DOI: 10.1038/jid.2014.288
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Accelerates Wound Healing by Regulating the Neuropilin-1/Smad3/NOX4 Pathway and ROS Production in Myofibroblasts

Abstract: Myofibroblasts have a key role in wound healing by secreting growth factors and chemoattractants to create new substrates and proteins in the extracellular matrix. We have found that galectin-1, a β-galactose-binding lectin involved in many physiological functions, induces myofibroblast activation; however, the mechanism remains unclear. Here, we reveal that galectin-1-null (Lgals1(-/-)) mice exhibited a delayed cutaneous wound healing response. Galectin-1 induced myofibroblast activation, migration, and proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 52 publications
3
50
0
Order By: Relevance
“…Galectins in oysters, such as Crassostrea virginica [9], Crassostrea gigas [10] and scallop Argopectens irradians [11], have been reported to play roles in immune response. Besides, galectins are implicated in epithelial cell adhesion and wound repair [6,12,13]. In the case of P. fucata, the cDNAs of a galectin with multiple carbohydrate-recognition domains, and a tandem-repeat galectin contained two tandem carbohydrate recognition domains have been cloned, and the mRNA expression levels were up-regulated after bacterial invasion [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Galectins in oysters, such as Crassostrea virginica [9], Crassostrea gigas [10] and scallop Argopectens irradians [11], have been reported to play roles in immune response. Besides, galectins are implicated in epithelial cell adhesion and wound repair [6,12,13]. In the case of P. fucata, the cDNAs of a galectin with multiple carbohydrate-recognition domains, and a tandem-repeat galectin contained two tandem carbohydrate recognition domains have been cloned, and the mRNA expression levels were up-regulated after bacterial invasion [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…There is controversy not only with respect to the presence of myofibroblasts in keloid tissues [2,4,8,44] but also over the conversion in vivo of dermal fibroblasts into myofibroblasts in wound healing induced by Gal-1 [24,26,45]. In fact, different studies in vivo have reported that myofibroblasts are the predominant cell type present in keloid tissues [4,44] while others report that they are absent [2,8] and that in animal models Gal-1 induces the conversion of dermal fibroblasts into myofibroblasts during wound healing [23,45].…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy not only regarding the presence of myofibroblasts in keloid tissues [2,4,8,44] but also regarding the conversion of fibroblasts into myofibroblasts by Gal-1 [24,26,45]; therefore, we sought to determine by double-immunofluorescence staining whether α-SM actin, the most common marker for myofibroblasts identification [46], was present in the fibroblasts of keloid tissues examined. Immunolocalization demonstrated that α-SM actin was completely absent in the fibroblasts expressing Gal-1 as well as in those that did not it (Fig.…”
Section: In Vivo Gal-1 Immunolocalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies using human cancer cell lines8 12 14 24 or animal tissue25 revealed that Gal-1 promotes angiogenesis and lymphangiogenesis, and induces apoptosis of activated T cells 5 13. These studies demonstrated that inhibition of Gal-1 promotes immunosuppression and reduces tumour metastasis 25–27.…”
Section: Introductionmentioning
confidence: 99%